The executive statutes of the Intellectual property rights protection law = اللائحة التنفيذية لقانون حماية حقوق الملكية الفكرية - Egypt. (2025)
Prime minister’s decree no. 1366 of the year 2003 promulgating the executive statutes of books 1,2 and 4 of the intellectual property rights protection law as promulgated by law no. 82 of the year 2002 – book 1: letters patent and utility designs and integrated circuits schematic designs and undisclosed information – book 2: trade marks and data, the geographical indices and the industrial drawings and designs – book 4: botanic items قرار رئيس مجلس الوزراء رقم 1366 لسنة 2003 باصدار اللائحة التنفيذية للكتب الاول والثانى والرابع من قانون حماية حقوق الملكية الفكرية الصادر بالقانون رقم 82 لسنة 2002 – الكتاب الاول براءات الاختراع و نماذج المنفعة، والتصميمات التخطيطية للدوائر المتكاملة والمعلومات غير المفصح عنها -- الكتاب الثانى العلامات والبيانات التجارية والمؤشرات الجغرافية والتصميمات والنماذج الصناعية – الكتاب الرابع الاصناف النباتية